Differences in physicians’ ratings of work stressors and resources associated with digital transformation: cross-sectional study - Wekenborg, Magdalena Katharina; Förster, Katharina; Schweden, Florian; Weidemann, Robin Ravi; Bechtolsheim, Felix, Freiherr von; Kirschbaum, Clemens; Weitz, Jürgen; Ditzen, Beate (Journal of medical internet research, 2024)
Background: The emergence of the COVID-19 pandemic rapidly accelerated the need and implementation of digital innovations, especially in medicine. - Objective: To gain a better understanding of the stress associated with digital transformation in physicians, this study aims to identify working conditions that are stress relevant for physicians and differ in dependence on digital transformation. In addition, we examined the potential role of individual characteristics (ie, age, gender, and actual implementation of a digital innovation within the last 3 years) in digitalization-associated differences in these working conditions. - Methods: Cross-sectional web-based questionnaire data of 268 physicians (mean age 40.9, SD 12.3 y; n=150, 56% women) in Germany were analyzed. Physicians rated their chronic stress level and 11 relevant working conditions (ie, work stressors such as time pressure and work resources such as influence on sequence) both before and after either a fictional or real implementation of a relevant digital transformation at their workplace. In addition, a subsample of individuals (60; n=33, 55% women) submitted self-collected hair samples for cortisol analysis. - Results: The stress relevance of the selected working conditions was confirmed by significant correlations with self-rated chronic stress and hair cortisol levels (hair F) within the sample, all of them in the expected direction (P values between .01 and <.001). Multilevel modeling revealed significant differences associated with digital transformation in the rating of 8 (73%) out of 11 working conditions. More precisely, digital transformation was associated with potentially stress-enhancing effects in 6 working conditions (ie, influence on procedures and complexity of tasks) and stress-reducing effects in 2 other working conditions (ie, perceived workload and time pressure). Younger individuals, women, and individuals whose workplaces have implemented digital innovations tended to perceive digitalization-related differences in working conditions as rather stress-reducing. - Conclusions: Our study lays the foundation for future hypothesis-based longitudinal research by identifying those working conditions that are stress relevant for physicians and prone to differ as a function of digital transformation and individual characteristics.